4-Benzyl-6-bromo-2-phenyl-4H-imidazo[4,5-b]pyridine - Ouzidan, Y.; Obbade, S.; Capet, F.; Essassi, E.M.; Ng, S.W. (International Union of Crystallography, 2010)
The imidazopyridine fused ring in the title compound, C(19)H(14)BrN(3), is almost coplanar with the phenyl ring at the 2-position of the five-membered ring [dihedral angle = 2.4 (1). The crystal structure features short Br center dot center dot center dot Br contacts [3.562 (1) angstrom].